Knowledge regarding attention deficit hyperactivity disorder of children among school teachers at Lalitpur - Bhattarai, Lata; Sharma, Mamata (Journal of Chitwan Medical College, 2019)
Background: Attention deficit hyperactivity disorder (ADHD) is one of the most common mental disorders affecting children. ADHD knowledge among teachers helps managing such children. This study aimed to assess the knowledge regarding ADHD of children among school teachers at Lalitpur, Nepal. Methods: A descriptive cross-sectional study was conducted among 124 primary school teachers in 19 government schools of Lalitpur Metropolitan City. A standard tool “Knowledge of Attention Deficit Disorders Scale (KADDS)” was used, which is valid and reliable tool designed by Sciutto and colleagues. Data were collected from 2017/06/20 to 2017/07/20. Data were analyzed using descriptive (frequency, percentage, mean and standard deviation) and inferential statistics (chi square test) for frequency distribution and association between levels of knowledge regarding ADHD with selected variables. Results: Eighty-five (68.5%) female and 39 (31.5%) male teachers with the mean age 41.85 ± 8.80 years (range 18 to 58 years) were enrolled. Majority teachers were married (94.4%) and from urban area (75%) with bachelor’s degree (37.9%) as their educational qualification and 11 to 20 years of teaching experiences (42.74%). The significant influencing variables were educational qualification (p = 0.009), type of service (p = 0.018), teaching experiences (p = 0.002), in-service education on ADHD (p = 0.004) and experience with ADHD students (p = 0.001). The study showed that 94 (75.8%) teachers had poor knowledge. Conclusions: It was concluded that three fourth of the teachers had poor knowledge about ADHD. Teachers knowledge will help to identify, refer and help in management of children with ADHD.